Alternatives to potentially inappropriate medications for use in e-prescribing software: triggers and treatment algorithms. Issue 10 (30th June 2011) - Hume, Anne L; Quilliam, Brian J; Goldman, Roberta; Eaton, Charles; Lapane, Kate L
Abstract : Objective: To describe the development of evidence-based electronic prescribing (e-prescribing) triggers and treatment algorithms for potentially inappropriate medications (PIMs) for older adults. Design: Literature review, expert panel and focus group. Setting: Primary care with access to e-prescribing systems. Participants: Primary care physicians using e-prescribing systems receiving medication history. Interventions: Standardised treatment algorithms for clinicians attempting to prescribe PIMs for older patients. Main outcome measure: Development of 15 treatment algorithms suggesting alternative therapies. Results: Evidence-based treatment algorithms were well received by primary care physicians. Providing alternatives to PIMs would make it easier for physicians to change decisions at the point of prescribing. Conclusion: Prospectively identifying older persons receiving PIMs or with adherence issues and providing feasible interventions may prevent adverse drug events.